Adsorption Properties of Low-Cost Biomaterial Derived from Prunus amygdalus L. for Dye Removal from Water - Fatih Deniz (The Scientific World Journal)
The capability of Prunus amygdalus L. (almond) shell for dye removal from aqueous solutions was investigated and methyl orange was used as a model compound. The effects of operational parameters including pH, ionic strength, adsorbent concentration and mesh size, dye concentration, contact time, and temperature on the removal of dye were evaluated. The adsorption kinetics conformed to the pseudo-second-order kinetic model. The equilibrium data pointed out excellent fit to the Langmuir isotherm model with maximum monolayer adsorption capacity of 41.34 mg g−1 at 293 K. Thermodynamic analysis proved a spontaneous, favorable, and exothermic process. It can be concluded that almond shell might be a potential low-cost adsorbent for methyl orange removal from aqueous media.